Experimental approach to obtaining subcutaneous xenograft of non-small cell lung cancer - E. A. Lukbanova; M. V. Mindar; E. A. Dzhenkova; A. Yu. Maksimov; A. S. Goncharova; Yu. S. Shatova; A. A. Maslov; A. V. Shaposhnikov; E. V. Zaikina; Yu. N. Lazutin (Исследования и практика в медицине)
Purpose of the study. Was was the creation of a Patient Derived Xenograft (PDX) model of non‑small cell lung cancer in immunodeficient mice adapted to growth in immunodeficient mice.Materials and methods. The study was performed using the tumor material from 14 donors implanted subcutaneously to 132 immunodeficient Balb/c Nude mice. Xenografts were maintained until the third passage. PDXs in the third passage from 3 patients were used to assess the model sensitivity to cisplatin. A histological analysis and genetic tests for the presence of EGFR mutations were performed for donor tumors from 3 patients and the corresponding xenografts in the third passage.Results. We observed a noticeable PDX growth already on the 8th day after the tumor material implantation. Successful xenograft engraftment was noted in 21 of 42 mice (50 %), which were rather successful results. A comparative histological analysis of tumor material from 3 patients showed that the PDX models retained the original histotype. We also demonstrated the identity of the EGFR mutations in the established xenografts from 3 patients and the donor tumors, which proved the value of these PDX models for preclinical studies of substances with potential antitumor activity. The analysis of the xenograft sensitivity to cytostatic cisplatin showed a statistically significant decrease in the growth rate in the xenografts obtained from 2 out of 3 patients, in comparison with the control.Conclusions. The created PDX models can be recommended as test systems for preclinical studies of the effectiveness of new pharmacological substances with potential antitumor activity.